Leishmaniases in the European Union and Neighboring Countries - Berriatua, Eduardo (2021)
A questionnaire survey of animal and human health authorities in Europe revealed that leishmaniases are not notifiable in all countries with autochthonous cases. Few countries implement surveillance and control targeting both animal and human infections. Leishmaniases are considered emergent diseases in most countries, and lack of resources is a challenge for control.